Carbon control method for producing vanadium-aluminum alloy by using graphite crucible
Through the use of graphite 坩埚 in the production of aluminum alloy and conduct regular cleaning and coating electric magnesium fire mud coating, combined with sand spraying and polishing, the problem of high carbon content of aluminum alloy is solved. Carbon content of cricket aluminum alloy.
Patent Information
- Application Number
- CN202411734529.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-28
AI Technical Summary
In the existing vanadium aluminum alloy production process, vanadium aluminum alloy has a high carbon content, which is difficult to meet the purity requirements of large-scale industrial production.
Graphite is used as a smelting furnace, which can prevent the inner wall from erosion and extend the service life of the 坩埚 by regular cleaning and coating of electric magnesium fire mud. After the smelting, sandblast and polish the surface of the aluminum alloy, reduce the carbon content and remove the surface oxide and other residues.
Effectively reduce the carbon content of aluminum alloy, improve the purity and quality of the product, extend the service life of graphite, and reduce energy consumption and production costs.
Smart Images

Figure CN119372508A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgy, and in particular to a carbon control method for producing vanadium-aluminum alloy in a graphite crucible. Background Art
[0002] Thermite is a method of obtaining a single substance of a high melting point metal by using the reducing property of aluminum. Thermite refers to a mixture of aluminum and metal oxides. After mixing aluminum powder with a certain amount of high melting point metal oxides (such as iron oxide, etc.), it is ignited with a magnesium bar. It can be seen that the aluminum powder reacts violently at a high temperature, releasing a large amount of heat and emitting a dazzling light. The product is a single substance of aluminum oxide and the high melting point metal. The thermite reaction is very intense, so it is difficult to extinguish after ignition, and it is difficult to control the reaction process after ignition. The reaction is to load the furnace charge and quickly generate high temperature (1700℃~3000℃) at the moment of ignition to make the furnace charge in a molten state, and then the alloy is refined. The advantage of this smelting method is that it does not require the input of electric heat, has low energy consumption, and has a lower production cost than the electric arc furnace smelting method.
[0003] Vanadium aluminum alloy is a basic raw material for titanium alloys. It is currently the second largest application area after the application of vanadium in steel. Ti-6Al-4V and Ti-8Al-1Mo-1V, these two titanium alloys account for 50% of the titanium alloy market and are mainly used in the production of jet engines, high-speed aircraft frames and rocket engine casings. The vanadium used in the production of titanium alloys is added in the form of vanadium aluminum alloys. Japan, the United States, the United Kingdom and other countries are also further increasing the application research of vanadium-containing titanium alloys in civilian industries.
[0004] At present, the production process of vanadium-aluminum alloy generally uses vanadium pentoxide as raw material and adopts aluminothermic method to produce vanadium-aluminum alloy. Since vanadium pentoxide reacts with metal aluminum to release a large amount of heat, the heat is greatly excessive, making the reaction explosive, which is enough to raise the temperature of the system to more than 3000℃ under adiabatic conditions. Therefore, a certain amount of inert substances (commonly known as heat removers) are usually added to the charge to control the reaction speed and the temperature rise of the reaction products. Since the heat remover always contains a certain amount of Fe, Si, P and heavy metal elements, the impurity content in the produced vanadium-aluminum alloy is relatively high.
[0005] The invention patent application with application publication number CN101818270A discloses a method for preparing a vanadium-aluminum alloy material. The method weighs 20% to 33.1% Al and 50% to 66.9% V2O5 in powder form by mass percentage, mixes them in a ball mill for 8 to 16 hours, places them in a copper mold and compacts them with a press at a pressure of 60 to 80 MPa, places the mold with the pressed reaction material in an aluminum heat reaction vessel, places an igniter on the material, blows out the residual air with an inert gas, and heats to about 300°C under argon protection of 2 to 7 MPa to react to obtain a vanadium-aluminum alloy, wherein, by mass percentage, V is 75% to 95%, Al is 5.0% to 25.0%, S content is about 0.15%, and Fe content is about 0.50%. Obviously, in the above process, the impurity content of Fe and S in the obtained product is relatively high, because some impurities will be introduced by mixing in the ball mill for 8 to 16 hours. In addition, since the thermite reaction is carried out in a closed pressure vessel, the output of vanadium-aluminum alloy is greatly limited. In addition, since the equipment is required to have strong pressure resistance, the manufacturing cost will be increased.
[0006] The invention patent application with application publication number CN104611601A discloses a vanadium aluminum alloy and a preparation method thereof, which uses vanadium pentoxide and aluminum particles as raw materials, adopts a one-time laying method, and ignites and reduces to obtain a vanadium aluminum alloy; wherein the weight ratio of vanadium pentoxide to aluminum particles is 1.15 to 1.8:1; and a graphite crucible with an inner wall coated with fused magnesium fire clay and a lid with holes is used as a smelting furnace. The above application uses a graphite crucible as a smelting furnace, and its inner wall is coated with fused magnesium fire clay and has holes. This structure may cause part of the carbon element to migrate from the graphite crucible to the vanadium aluminum alloy during the smelting process, especially under high temperature conditions, the migration of carbon elements is more significant. Based on this, the existing technology still needs to be improved. Summary of the invention
[0007] In view of this, the present invention proposes a method for controlling carbon in the production of vanadium-aluminum alloy using a graphite crucible, which can at least solve the technical problem of high carbon content in vanadium-aluminum alloy produced by the existing vanadium-aluminum alloy production process.
[0008] A method for controlling carbon in a graphite crucible to produce a vanadium-aluminum alloy comprises the following steps: S1, putting vanadium pentoxide and aluminum particles in a preset ratio into a graphite crucible; S2, ignition reduction, aluminum hot smelting, to produce vanadium aluminum alloy and slag; S3, after the smelting is completed, the surface of the vanadium-aluminum alloy is sandblasted and polished.
[0009] Wherein, after the graphite crucible is used for a preset number of times, the inner wall of the loose erosion layer is cleaned and coated with a fused magnesium fire clay coating, and the crust layer formed on the bottom of the graphite crucible is retained until the service life of the crucible expires.
[0010] In some embodiments, the crust layer is formed on the bottom of the graphite crucible after being used for 3 to 5 times.
[0011] In some embodiments, the inner wall of the loose erosion layer of the graphite crucible is cleaned and coated with a fused magnesium fire clay coating after each use of 5 to 10 times. By regularly cleaning the inner wall of the graphite crucible and coating it with a fused magnesium fire clay coating, further erosion of the inner wall of the graphite crucible can be prevented, and its service life can be extended, thereby reducing the frequency of replacing the crucible and improving production efficiency.
[0012] In some embodiments, the fused magnesium fire clay coating is applied to the side wall of the graphite crucible, and the coating thickness is 1-5 mm. This effectively prevents the inner wall of the graphite crucible from being corroded by the molten metal and slag, thereby extending the service life of the crucible. It also helps to reduce heat loss by maintaining the integrity of the inner wall of the graphite crucible, thereby reducing energy consumption.
[0013] In some embodiments, the weight ratio of vanadium pentoxide to aluminum particles is 1.16 to 1.67: 1. By using an excess of aluminum particles, a vanadium-aluminum alloy can be formed by fusing the aluminum particles with metallic vanadium during the reduction reaction.
[0014] In some embodiments, the heat of aluminothermic smelting is 3250-3350 kJ / kg, which can ensure the stability and efficiency of the reaction.
[0015] In some embodiments, the blasting material is aluminum particles without introducing other metals, so that a vanadium aluminum alloy with a lower carbon content can be obtained.
[0016] In some embodiments, the Na2O content + K2O content in vanadium pentoxide is ≤ 0.2% to reduce the generation of pores during alloy smelting and improve the purity and quality of vanadium aluminum alloy.
[0017] In some embodiments, the ignition agent used for ignition reduction is barium peroxide, and magnesium rods are used as ignition materials to provide a high-temperature environment and quickly ignite the thermite smelting reaction.
[0018] In some embodiments, the method for controlling carbon in vanadium-aluminum alloy produced by using a graphite crucible further includes: S4, allowing the vanadium-aluminum alloy to stand for 30 to 60 minutes after being sandblasted and polished, which helps release stress in the vanadium-aluminum alloy, reduces residual stress inside the material, and prevents deformation or cracking during subsequent processing or use.
[0019] The beneficial effects of the present invention are as follows: the invention uses a graphite crucible as a smelting furnace to smelt vanadium-aluminum alloys, which not only fully utilizes the advantage of the graphite crucible in reducing the apparent defects of the vanadium-aluminum alloy, but also avoids the disadvantage that the carbon content of the vanadium-aluminum alloy is easily exceeded by adopting the innovation of the operating process, and the obtained product fully meets the requirements of large-scale industrial production. By regularly cleaning and coating the fused magnesium fire mud coating, the erosion of the inner wall of the graphite crucible can be effectively prevented, and its service life can be extended, thereby reducing the frequency of replacing the crucible and improving production efficiency. By sandblasting the surface of the vanadium-aluminum alloy after the smelting is completed, the carbon content can be effectively reduced. By polishing the surface of the vanadium-aluminum alloy, the oxide scale, oil stains and other residues on the surface of the alloy can be effectively removed, making the surface cleaner. By retaining the crust layer formed at the bottom of the graphite crucible until the service life of the crucible expires, the contact area between graphite and the alloy liquid can be effectively reduced, the reaction environment can be stabilized, and the quality of the vanadium-aluminum alloy can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0021] Figure 1 A flow chart of a method for controlling carbon in a vanadium-aluminum alloy produced using a graphite crucible provided in one embodiment of the present invention. DETAILED DESCRIPTION
[0022] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in combination with specific embodiments and with reference to the accompanying drawings.
[0023] The present invention provides a method for controlling carbon in a graphite crucible for producing vanadium-aluminum alloy, comprising the following steps: S1, putting vanadium pentoxide and aluminum particles in a preset ratio into a graphite crucible; S2, ignition reduction, aluminum hot smelting, to produce vanadium aluminum alloy and slag; S3, after the smelting is completed, the surface of the vanadium-aluminum alloy is subjected to sandblasting treatment and polishing. Specifically, compressed air is used as a power to form a high-speed jet beam to spray the abrasive at high speed onto the surface of the vanadium-aluminum alloy.
[0024] Among them, after the graphite crucible is used for a preset number of times, the inner wall of the loose erosion layer is cleaned and coated with a fused magnesium fire clay coating, and the crust layer formed on the bottom of the graphite crucible is retained until the service life of the crucible expires, so as to reduce the contact area between the graphite and the alloy liquid.
[0025] Compared with the traditional process, the vanadium-aluminum alloy preparation method of the present invention adopts a graphite crucible as a smelting furnace to smelt the vanadium-aluminum alloy, which not only fully utilizes the advantage of the graphite crucible in reducing the apparent defects of the vanadium-aluminum alloy, but also avoids the disadvantage that the carbon content of the vanadium-aluminum alloy is easily exceeded by adopting the innovation of the operation process. By regularly cleaning and coating the fused magnesium fire mud coating, the erosion of the inner wall of the graphite crucible can be effectively prevented, and its service life can be extended, thereby reducing the frequency of replacing the crucible and improving production efficiency. By sandblasting the surface of the vanadium-aluminum alloy after the smelting is completed, the carbon content can be effectively reduced. By polishing the surface of the vanadium-aluminum alloy, the oxide scale, oil stains and other residues on the surface of the alloy can be effectively removed, making the surface cleaner. By retaining the crust layer formed at the bottom of the graphite crucible until the service life of the crucible expires, the contact area between graphite and the alloy liquid can be effectively reduced, the reaction environment can be stabilized, and the quality of the vanadium-aluminum alloy can be improved.
[0026] In some embodiments, a crust layer is formed on the bottom of the graphite crucible after being used for 3 to 5 times. The formed crust layer helps to reduce the contact area between the graphite and the alloy liquid, further reducing the carbon content of the vanadium aluminum alloy.
[0027] In some embodiments, the inner wall of the loose erosion layer of the graphite crucible is cleaned and coated with a fused magnesium fire clay coating after each 5 to 10 uses. Since the main component of the fused magnesium fire clay coating is fused magnesia, this material can withstand extremely high temperatures and is suitable for use in high temperature environments. It can effectively resist the erosion of molten metal and slag and protect the inner wall of the graphite crucible from damage. And the coating has good adhesion to the inner wall of the graphite crucible and is not easy to fall off. By regularly cleaning the inner wall of the graphite crucible and coating it with a fused magnesium fire clay coating, further erosion of the inner wall of the graphite crucible can be prevented, extending its service life, thereby reducing the frequency of replacing the crucible and improving production efficiency.
[0028] In some embodiments, the fused magnesium fire clay coating is applied to the side wall of the graphite crucible with a coating thickness of 1 to 5 mm to effectively prevent the inner wall of the graphite crucible from being corroded by the molten metal and slag, thereby extending the service life of the crucible. It also helps to reduce heat loss by maintaining the integrity of the inner wall of the graphite crucible, thereby reducing energy consumption.
[0029] In some embodiments, the weight ratio of vanadium pentoxide to aluminum particles is 1.16 to 1.67: 1. Excess aluminum particles are used to form a vanadium aluminum alloy by fusing the aluminum particles with metallic vanadium during the reduction reaction. Specifically, under normal circumstances, the weight ratio of vanadium pentoxide to aluminum particles is 2: 1. In this application, excess aluminum is used to fuse with metallic vanadium to form a vanadium aluminum alloy.
[0030] In some embodiments, the heat of aluminothermic smelting is 3250-3350 kJ / kg, which can ensure the stability and efficiency of the reaction. This heat range helps to maintain a suitable temperature environment, so that vanadium pentoxide and aluminum particles react fully, thereby improving production efficiency, and can effectively reduce impurity generation and improve the quality of vanadium aluminum alloy.
[0031] In some embodiments, the raw material for sandblasting is aluminum particles. Aluminum particles are used as sandblasting raw materials because of their high sphericity, low impurity content, and high proportion of active aluminum (more than 98%), which makes the sandblasting process more efficient. The high purity and uniform particle size distribution of aluminum particles help to achieve faster surface treatment, thereby improving production efficiency, and without introducing other metals, vanadium aluminum alloys with lower carbon content can be obtained.
[0032] In some embodiments, the content of Na2O + K2O in vanadium pentoxide is ≤0.2%. In order to reduce the generation of pores during the alloy smelting process, it is necessary to reduce the content of such low-melting-point substances, effectively reduce the adverse effects of impurities on the smelting process, and improve the purity and quality of the vanadium aluminum alloy.
[0033] In some embodiments, in step S2, the ignition reduction ignition agent is barium peroxide, and magnesium strips are used as ignition materials. By using barium peroxide and magnesium strips as ignition agents, a high temperature environment can be provided to quickly ignite the aluminum thermal smelting reaction, and it is conducive to the full reaction between vanadium pentoxide and aluminum particles, thereby improving the purity and quality of vanadium aluminum alloy and ensuring the stability and consistency of the reaction.
[0034] In some embodiments, the method for controlling carbon in vanadium-aluminum alloy produced by graphite crucible further includes: step S4, allowing the vanadium-aluminum alloy after sandblasting and polishing to stand for 30 to 60 minutes. During the sandblasting and polishing process, certain mechanical stress may be generated on the surface of the material. Standing for a period of time helps to release these stresses, reduce the residual stress inside the material, and prevent deformation or cracking during subsequent processing or use. And standing still allows the temperature of the material to gradually balance, avoiding internal stress and structural unevenness caused by temperature differences.
[0035] In order to better illustrate this solution, several specific embodiments and comparative examples are provided below: Example 1 Take 100kg of vanadium pentoxide, the content of Na2O + K2O in the vanadium pentoxide is ≤0.2%, 60kg of aluminum particles are used as raw materials, the weight ratio of vanadium pentoxide to aluminum particles is 1.67:1, a graphite crucible is used as the smelting furnace body, the graphite crucible is coated with fused magnesium fire mud on the side wall after 5 heats, and the bottom of the graphite crucible has a crust layer formed at the bottom of the crucible after 3 heats. After the smelting is completed, the surface of the alloy cake is sandblasted to reduce the carbon content of the alloy cake surface into the finished product. After the operation is completed, it is left to stand for 30 minutes to obtain 62.5kg of vanadium aluminum alloy products, which contain 0.21wt% carbon.
[0036] Comparative Example 1 Take 100kg of vanadium pentoxide, the content of Na2O + K2O in the vanadium pentoxide is ≤0.2%, 60kg of aluminum particles are used as raw materials, the weight ratio of vanadium pentoxide to aluminum particles is 1.67:1, and an ordinary graphite crucible (without coating and crust retention) is used as the smelting furnace body, and no coating and crust retention operations are performed. After the smelting is completed, it is allowed to stand for 30 minutes to obtain 62.4kg of vanadium aluminum alloy product, which contains 0.25wt% carbon.
[0037] Example 2 Take 100kg of vanadium pentoxide, the content of Na2O + K2O in the vanadium pentoxide is ≤0.2%, 63.7kg of aluminum particles are used as raw materials, the weight ratio of vanadium pentoxide to aluminum particles is 1.58:1, a graphite crucible is used as the smelting furnace body, the graphite crucible is coated with fused magnesium fire mud on the side wall after 6 heats, and the bottom of the graphite crucible has a crust layer formed at the bottom of the crucible after 4 heats. After the smelting is completed, the surface of the alloy cake is sandblasted to reduce the carbon content of the alloy cake surface into the finished product. After the operation is completed, it is left to stand for 30 minutes to obtain 64.88kg of vanadium aluminum alloy products, which contain 0.20wt% carbon.
[0038] Comparative Example 2 Take 100kg of vanadium pentoxide, the content of Na2O + K2O in the vanadium pentoxide is ≤0.2%, 63.7kg of aluminum particles are used as raw materials, the weight ratio of vanadium pentoxide to aluminum particles is 1.58:1, and an ordinary graphite crucible is used as the smelting furnace body. No coating or crust layer retention operation is performed. After the smelting is completed, it is allowed to stand for 30 minutes to obtain 64.86kg of vanadium aluminum alloy product, which contains 0.25wt% carbon.
[0039] Example 3 Take 100kg of vanadium pentoxide, the content of Na2O + K2O in the vanadium pentoxide is ≤0.2%, 83.4kg of aluminum particles are used as raw materials, the weight ratio of vanadium pentoxide to aluminum particles is 1.2:1, a graphite crucible is used as the smelting furnace body, the graphite crucible is coated with fused magnesium fire mud on the side wall after 7 heats, and the bottom of the graphite crucible has a crust layer formed at the bottom of the crucible after 4 heats. After the smelting is completed, the surface of the alloy cake is sandblasted to reduce the carbon content of the alloy cake surface into the finished product. After the operation is completed, it is left to stand for 30 minutes to obtain 87.7kg of vanadium aluminum alloy products, which contain 0.08wt% carbon.
[0040] Comparative Example 3 Take 100kg of vanadium pentoxide, the content of Na2O + K2O in the vanadium pentoxide is ≤0.2%, 83.4kg of aluminum particles are used as raw materials, the weight ratio of vanadium pentoxide to aluminum particles is 1.2:1, and an ordinary graphite crucible is used as the smelting furnace body. No coating or crust layer retention operation is performed. After the smelting is completed, it is allowed to stand for 30 minutes to obtain 87.6kg of vanadium aluminum alloy product, which contains 0.1wt% carbon.
[0041] Example 4 Take 100kg of vanadium pentoxide, the content of Na2O + K2O in the vanadium pentoxide is ≤0.2%, 86kg of aluminum particles are used as raw materials, the weight ratio of vanadium pentoxide to aluminum particles is 1.16:1, a graphite crucible is used as the smelting furnace body, the graphite crucible is coated with fused magnesium fire mud on the side wall after 10 heats, and the bottom of the graphite crucible has a crust layer formed at the bottom of the crucible after 5 heats. After the smelting is completed, the surface of the alloy cake is sandblasted to reduce the carbon content of the alloy cake surface into the finished product. After the operation is completed, it is left to stand for 30 minutes to obtain 96.07kg of vanadium aluminum alloy products, which contain 0.08wt% carbon.
[0042] Comparative Example 4 Take 100kg of vanadium pentoxide, the content of Na2O + K2O in the vanadium pentoxide is ≤0.2%, 86kg of aluminum particles are used as raw materials, the weight ratio of vanadium pentoxide to aluminum particles is 1.16:1, and an ordinary graphite crucible is used as the smelting furnace body. No coating or crust layer retention operation is performed. After the smelting is completed, it is allowed to stand for 30 minutes to obtain 95.05kg of vanadium aluminum alloy product, which contains 0.12wt% carbon.
[0043] The carbon content of the vanadium-aluminum alloy product obtained by using the graphite crucible as the smelting furnace body is reduced compared with that before the process is implemented, and the product quality is significantly improved.
[0044] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0045] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A method for controlling carbon in graphite crucible production of vanadium aluminum alloy, characterized in that: The following steps are involved: S1, putting vanadium pentoxide and aluminum particles in a preset ratio into a graphite crucible; S2, ignition reduction, aluminum hot smelting, to produce vanadium aluminum alloy and slag; S3, sandblasting the surface of the vanadium aluminum alloy and polishing the surface of the vanadium aluminum alloy; Wherein, after the graphite crucible is used for a preset number of times, the inner wall of the loose erosion layer is cleaned and coated with a fused magnesium fire clay coating, and the crust layer formed on the bottom of the graphite crucible is retained until the service life of the crucible expires.
2. The method for controlling carbon in vanadium-aluminum alloy produced by using graphite crucible according to claim 1, characterized in that: Also includes: The crust layer is formed on the bottom of the graphite crucible after being used for 3 to 5 times.
3. The method for controlling carbon in vanadium-aluminum alloy produced by using graphite crucible according to claim 1, characterized in that: After the graphite crucible is used 5 to 10 times, the inner wall of the loose erosion layer is cleaned and coated with a fused magnesium fireclay coating.
4. The method for controlling carbon in vanadium-aluminum alloy produced by using graphite crucible according to claim 3, characterized in that: The fused magnesium fireclay coating is coated on the side wall of the graphite crucible, and the coating thickness is 1-5 mm.
5. The carbon control method for producing vanadium aluminum alloy in graphite crucible according to claim 1, characterized in that: The weight ratio of the vanadium pentoxide to the aluminum particles is 1.16-1.67:
1.
6. The carbon control method for producing vanadium-aluminum alloy in graphite crucible according to claim 1, characterized in that: The heat of the aluminothermic smelting is 3250~3350kJ / kg.
7. The carbon control method for producing vanadium-aluminum alloy in graphite crucible according to claim 2, characterized in that: The blasting material is aluminum particles.
8. The method for controlling carbon in vanadium-aluminum alloy produced by using graphite crucible according to claim 1, characterized in that: The Na2O content + K2O content in the vanadium pentoxide is ≤0.2%.
9. The carbon control method for producing vanadium-aluminum alloy in graphite crucible according to claim 1, characterized in that: Step S2, the ignition agent used for ignition reduction is barium peroxide, and magnesium strips are used as ignition materials.
10. The carbon control method for producing vanadium aluminum alloy in graphite crucible according to claim 2, characterized in that: Also includes: S4, leaving the sandblasted and polished vanadium-aluminum alloy to stand for 30 to 60 minutes.
Citation Information
Patent Citations
Method for preparing vanadium-aluminum alloy material
CN101818270A
Vanadium-aluminum alloy and preparation method thereof
CN104611601A